Social and Cultural Barriers Reported by STEM International Graduate Students of Color - RODRIGUEZ, MIGUEL; ROMAN, BRIAN ZAMMARRIPPA; MOHAMED, MIRNA; BARTHELEMY, RAMON (Journal of International Students, 2024)
This article explores international students’ experiences in their graduate STEM programs at predominantly white US institutions through in-depth qualitative interviews and thematic analysis. International students reported encountering social and cultural barriers with American peers and sometimes even with other international students. These barriers include language, popular cultural, and social norms. Some students, who were less culturally represented in their cohorts, felt isolated but later found other people outside of their departments, often people from their same cultural background. The experiences of our participants varied by the representation of their culture in their departments, where students from less represented countries experienced more isolation. Connections to current acculturation theory will be discussed, as well as further implications and possible solutions for increasing intercultural exchanges.